2020
DOI: 10.2174/1567205016666190816114838
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Vestibular Loss in Mild Cognitive Impairment and Alzheimer’s Disease

Abstract: Background/Aims:: Recent evidence has shown that Alzheimer’s Disease (AD) patients have reduced vestibular function relative to healthy controls. In this study, we evaluated whether patients with Mild Cognitive Impairment (MCI) also have reduced vestibular function relative to controls, and compared the level of vestibular impairment between MCI and AD patients. Methods:: Vestibular physiologic function was assessed in 77 patients (26 MCI, 51 AD) and 295 matched controls using 3 clinical vestibular tests. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 49 publications
0
32
0
1
Order By: Relevance
“…This result suggests the possibility that age-related impairment of spatial memory, as well as impairment of saccular function, may be related to a decrease in hippocampal volume. In their most recent study, Wei et al (2019), studied 26 patients with MCI, 51 with AD and 295 matched control subjects and evaluated their cVEMPs, oVEMPs and VOR gain. They found that with increased cognitive impairment, there was a significant decrease in cVEMP and oVEMP responses.…”
Section: Evidence For Otolithic Involvement In Spatial Memory In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests the possibility that age-related impairment of spatial memory, as well as impairment of saccular function, may be related to a decrease in hippocampal volume. In their most recent study, Wei et al (2019), studied 26 patients with MCI, 51 with AD and 295 matched control subjects and evaluated their cVEMPs, oVEMPs and VOR gain. They found that with increased cognitive impairment, there was a significant decrease in cVEMP and oVEMP responses.…”
Section: Evidence For Otolithic Involvement In Spatial Memory In Humansmentioning
confidence: 99%
“…This, in turn, is critical for the vestibular contribution to cognitive processes such as spatial memory (see Besnard et al, 2016; Smith, 2017 for reviews), the body representation of the self (see Mast et al, 2014; Lopez et al, 2015 for reviews), and even social cognition (see Deroualle and Lopez, 2014 for a review). Any role that the otoliths have in these processes is especially important since: aging is associated with reduced otolith function (e.g., Agrawal et al, 2012; Zu Eulenburg et al, 2017); impaired vestibular function and specifically otolithic function, has been recently associated with an increased risk of cognitive impairment and dementia (Aranda-Moreno and Jáuregui-Renaud, 2016; Harun et al, 2016; Wei et al, 2017, 2019; Xie et al, 2017; Kamil et al, 2018, in press; see Agrawal et al, 2019, in press, for a review); and otolithic lesions can occur in humans independently of lesions of the semi-circular canals (e.g., Manzari et al, 2014). In addition to other forms of dysfunction that can occur in the vestibular system (e.g., benign paroxysmal positional vertigo, vestibular migraine, Meniere’s disease, vestibular vertigo, vestibular neuritis, vestibular schwannomas, etc.…”
Section: Introductionmentioning
confidence: 99%
“…We will comprehensively assess the function of the entire peripheral vestibular system, including the semicircular canals and otolith organs (saccule and utricle). In prior studies, we observed that rates of both semicircular canal and otolith function impairment are higher in AD patients relative to age-matched controls [ 34 , 61 , 62 ]. We have previously published details of vestibular testing, including in patients with AD [ 31 , 32 , 63 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…En todos ellos se ha descrito una reducción del área de estabilidad del 35-62% independientemente de la edad. En los ancianos se producen también alteraciones visuales, propioceptivas, musculoesqueléticas y demencia, que, asociado a la toma de fármacos, reducen aún más ese área y favorecen las caídas [9][10][11][12].…”
Section: Cuadro Clínico Inicialunclassified